Juvenile Arthritis Patients Suffering from Chronic Inflammation Have Increased Activity of Both IDO and GTP-CH1 Pathways But Decreased BH4 Efficacy: Implications for Well-Being, Including Fatigue, Cognitive Impairment, Anxiety, and Depression - Gerdien A. H. Korte-Bouws; Eline Albers; Marije Voskamp; Hendrikus Hendriksen; Lidewij R. de Leeuw; Onur Güntürkün; Sytze de Roock; Sebastiaan J. Vastert; S. Mechiel Korte (MDPI AG, 2019)
Juvenile idiopathic arthritis (JIA) represents joint inflammation with an unknown cause that starts before the age of 16, resulting in stiff and painful joints. In addition, JIA patients often report symptoms of sickness behavior. Recent animal studies suggest that proinflammatory cytokines produce sickness behavior by increasing the activity of indoleamine-2,3-dioxygenase (IDO) and guanosinetriphosphate–cyclohydrolase-1 (GTP–CH1). Here, it is hypothesized that inflammation in JIA patients enhances the enzymatic activity of IDO and GTP-CH1 and decreases the co-factor tetrahydrobiopterin (BH4). These compounds play a crucial role in the synthesis and metabolism of neurotransmitters. The aim of our study was to reveal whether inflammation affects both the GTP-CH1 and IDO pathway in JIA patients. Serum samples were collected from twenty-four JIA patients. In these samples, the concentrations of tryptophan (TRP), kynurenine (KYN), tyrosine (TYR), neopterin, and phenylalanine (PHE) were measured. An HPLC method with electrochemical detection was developed to quantify tryptophan, kynurenine, and tyrosine. Neopterin and phenylalanine were quantified by ELISA. The KYN/TRP ratio was measured as an index of IDO activity, while the PHE/TYR ratio was measured as an index of BH4 activity. Neopterin concentrations were used as an indirect measure of GTP-CH1 activity. JIA patients with high disease activity showed higher levels of both neopterin and kynurenine, and a higher ratio of both KYN/TRP and PHE/TYR and lower tryptophan levels than clinically inactive patients. Altogether, these data support our hypothesis that inflammation increases the enzymatic activity of both IDO and GTP-CH1 but decreases the efficacy of the co-factor BH4. In the future, animal studies are needed to investigate whether inflammation-induced changes in these enzymatic pathways and co-factor BH4 lower the levels of the brain neurotransmitters glutamate, noradrenaline, dopamine, serotonin, and melatonin, and consequently, whether they may affect fatigue, cognition, anxiety, and depression. Understanding of these complex neuroimmune interactions provides new possibilities for Pharma-Food interventions to improve the quality of life of patients suffering from chronic inflammation.